2000
DOI: 10.1159/000029930
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Potential of Industrial Chemicals Using a Cultured Human Bioartificial Skin Model: Production of Interleukin 1α and Hydroxyeicosatetraenoic Acids

Abstract: Cytotoxicity assays using artificial skin are proposed as alternative methods for in vitro tests to minimize animals used in ocular and dermal irritation testing. The responses of the artificial skins were studied to a well-characterized chemical irritant, such as toluene, glutaraldehyde and sodium lauryl sulfate (SLS), and a nonirritant, such as polyethylene glycol. The evaluation of irritating and nonirritating test chemicals was also compared with responses seen in human dermal fibroblasts and human epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These authors also detected 15-HETE, whereas 5-HETE was not encountered. Other studies found that interleukin-1 increased the pro-duction of 12-and 15-HETE in human dermal fibroblasts (11,12). Additionally, it has been demonstrated that fibroblasts can respond to LOX products such as LTs or HETEs.…”
Section: Supplementary Abstract Cell Proliferation and Cell Cycle And Akmentioning
confidence: 95%
“…These authors also detected 15-HETE, whereas 5-HETE was not encountered. Other studies found that interleukin-1 increased the pro-duction of 12-and 15-HETE in human dermal fibroblasts (11,12). Additionally, it has been demonstrated that fibroblasts can respond to LOX products such as LTs or HETEs.…”
Section: Supplementary Abstract Cell Proliferation and Cell Cycle And Akmentioning
confidence: 95%
“…The medium was DMEM+10% FBS. For exposure to a known irritant [16,17], monolayers and macromasses were incubated in the presence of different concentrations of SDS (Sigma) or vehicle (water) added to the medium. Separate 80 μl volumes of 0, 0.1, 0.2, 0.3, 0.4 and 0.5% (w/v) SDS were added/ml of medium.…”
Section: Methodsmentioning
confidence: 99%
“…The monolayers and macromasses were exposed to the SDS for 24 h, after which cell mitochondrial function was assessed by the MTT [3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl‐2 H ‐tetrazolium bromide; Sigma–Aldrich] assay. For exposure to a known non‐irritant, monolayers and three‐dimensional constructs were incubated in the presence of different concentrations of PEG 400 [16] or vehicle (water) added to the medium. Separate 80 μl volumes of 0, 20, 40, 60, 80 and 100% (v/v) PEG 400 (Merck) were added/ml of medium.…”
Section: Methodsmentioning
confidence: 99%
“…Detergents destroy the barrier and stimulate the release of proinflammatory cytokines from keratinocytes. 42,43 Antiseptic alcohols have lipid-depleting detergents and irritating fragrances added to them. The picture is further obscured by large variations in the sensitivity to barrier problems from one person to another.…”
Section: Concerted Damagementioning
confidence: 99%